PCs for dummies - Gookin, Dan (--For dummies., 2016)
Overview: The bestselling PC reference on the planet-now available in its 13th edition. Completely updated to cover the latest technology and software, the 13th edition of PCs For Dummies tackles using a computer in friendly, human terms. Focusing on the needs of the beginning computer user, while also targeting those who are familiar with PCs, but need to get up to speed on the latest version of Windows. This hands-on guide takes the dread out of working with a personal computer. Leaving painful jargon and confusing terminology behind, it covers Windows 9 OS, connecting to and using services and data in the cloud, and so much more. Written by Dan Gookin, the original For Dummies author, it tells you how to make a PC purchase, what to look for in a new PC, how to work with the latest operating system, ways to protect your files, what you can do online, media management tips, and even basic topics you're probably too shy to ask a friend about. Determine what you need in a PC and how to set it up. -- Configure your PC, hook up a printer, and connect to the Internet. -- Find your way around Windows 9 OS with ease and confidence. -- Play movies and music, view photos, and explore social media. -- If you're a first-time PC user at home or at work or just need to brush up on the latest technological advancements, the new edition of this bestselling guide gets you up and running fast.